Cholecystocutaneous Fistula following Drainage of Parietal Abscess: A Rare Case Report (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Spontaneous perforation of gallbladder as a complication of biliary stones may lead to cholecystocutaneous abscess or fistula. Here we report a case of cholecystocutaneous fistula in a 50-year-old diabetic female patient who presented with a chronic discharging sinus on right upper abdomen with recurrent abscess formation which failed to heal despite repeated attempts at incision drainage and debridement. After evaluation the tract was explored and was found to be communicating with the fundus of the gall bladder. The whole fistula tract was excised along with cholecystectomy. DOI: http://dx.doi.org/10.3329/jbcps.v32i1.21037 J Bangladesh Coll Phys Surg 2014; 32: 37-40